The Chronicle of the Prohibition of Marriage in the Month of Suro: A Historical, Philosophical, and Community Education Analysis - Eka Mahargiani; Faiqqotus Sakdiyah; Sumarjoko Sumarjoko; Zainal Arifin (Yayasan Azhar Amanaa Yogyakarta, 2026)
The prohibition of marriage during the month of Suro remains a widely observed tradition in Javanese society, reflecting the dynamic interaction between local cultural practices and Islamic values, particularly in relation to Javanese cosmology and the concept of the sacredness of time. This study aims to examine the historical development and philosophical significance of the tradition of prohibiting marriage during the month of Suro from the perspectives of Javanese culture and Islamic law. The research employs a qualitative library research method using historical and philosophical approaches. Data were collected from historical literature, studies on Javanese culture, scholarly journal articles, and previous research, and were analyzed using a descriptive-analytical method. The findings indicate that this tradition constitutes a form of cultural heritage shaped through a long historical process, rooted in pre-Islamic cosmological beliefs and subsequently developed through the acculturation of Hindu-Buddhist and Islamic traditions. Philosophically, the tradition embodies values of prudence, respect for ancestors, and the preservation of harmony between human beings, nature, and the spiritual realm. Over time, its function has shifted from a binding social norm to a cultural symbol and an expression of local wisdom. From the perspective of Islamic law, there is no prohibition against marriage in any specific month. Therefore, this tradition may be regarded as a form of customary practice (ʿurf) that is acceptable as long as it does not contradict the principles of Islamic law.